Green roofs in planning guides: an evaluation on expected effects and instruments in municipal climate adaptation - Brenner, Jana; Hack, Jochen (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
With multifunctional measures such as the greening of roofs, green infrastructure makes a promising contribution to climate adaptation and the reducing of urban heat, even when there is high pressure on space and use. Despite a large number of planning guides that provide information on the selection, planning, and implementation on Green Infrastructure measures, the measures are not yet widely implemented across the board. The aim of this article is to evaluate the information on green roofs provided in 36 planning guides based on a qualitative content analysis and to provide an overview of the expected effects with regard to multifunctionality, spatial cooling effect, associated planning tools and funding opportunities. Spatial cooling impact, planning tools, and funding opportunities mentioned in the guides mainly relate to the building level. The development plan is mostly mentioned as a planning tool for roof greening. There is a lack of information on increasing the cooling impact of green roofs increasing on larger areas, as well as a lack of information on targeted, aerea-based and cross-level planning in the planning guides. To effectively reduce urban heat, it is necessary to integrate new findings into the planning guides and new approaches to using planning instruments and funding opportunities.
Keywords: Climate adaptation; Adaptive capacity; Green infrastructure; Urban heat island; Urban planning